Liposome-Encapsulated Antibiotics for the Therapy of Mycobacterial Infections - Metin Yıldırım; Nejat Düzgüneş (Antibiotics, 2025)
About a quarter of the world’s population is infected with Mycobacterium tuberculosis. Growing antibiotic resistance by this microorganism is a major problem in the therapy of the disease. M. avium-M. intracellulare that emerged as a major opportunistic infection of HIV/AIDS continues to afflict immunocompromised individuals. We describe the use of liposome-encapsulated antibiotics in the experimental and clinical therapy of mycobacterial infections, as well as recent experimental liposomal vaccines against tuberculosis. Liposome-mediated intravenous or inhalational delivery of antibiotics enhances the antibacterial effects of the drugs, particularly for infections of resident macrophages, where the liposomes are passively targeted. Despite experimental successes of liposomal antibiotics in the treatment of mycobacterial and other bacterial infections, applications of this method to the clinic have been lagging. This review underscores the significance of liposomes in the treatment of mycobacterial infections, encompassing their synthesis methods, limitations, and both preclinical and clinical studies, providing guidance for the development of future therapeutic approaches and innovative antimicrobial strategies.